Fertility preservation in oncology patients: A literature review examining current fertility preservation techniques and access to oncofertility services in Australia. (16th October 2019) - Robson, Danielle; Phua, Cheryl; Howard, Robyn; Marren, Anthony
Abstract : Background: In Australia, between the years 2010 and 2014, over 4500 adolescents and young adults (15–25 years old) were diagnosed with cancer. Treatment regimens are often gonadotoxic and are well known to induce ovarian and testicular failure. Oncofertility is an emerging discipline in obstetrics and gynaecology which seeks to preserve and restore the reproductive future of cancer patients. Aim: To perform a systematic literature review to assess the current fertility preservation techniques available to patients and examine access and uptake of fertility preservation in Australia. Materials and Methods: Electronic databases, including Medline, Cochrane Review, SCOPUS and CINHAL, were searched for peer‐reviewed publications and national guidelines examining oncofertility practices from 2008 to July 2018. Three hundred and seventy‐five articles were initially screened, with 158 articles for full text review and an additional five clinical guidelines were identified. Results: There is a paucity of Australian data on oncofertility with <50% of data included for analysis reflecting the Australian experience. The majority of primary research included retrospective papers with small cohort numbers. Key areas addressed included live birth outcomes, uptake of services and patient and physician perspectives on fertility preservation. Few articles sought to examine the positive and negative side effects of fertility preservation in oncology, social challenges of oncofertility and access to services worldwide. Conclusion: Oncofertility is an emerging discipline which seeks to provide safe, efficient and effective fertility preservation options for young adults and adolescents diagnosed with cancer. A multi‐disciplinary approach with collaborative communication with oncologists is key to providing this service within Australia.